Impact of three different processing methods on the digestibility and allergenicity of Chinese mitten crab (Eriocheir sinensis) tropomyosin - Yufeng Lu; Huafeng Cheng; Shaotong Jiang; Lin Lin; Jianfeng Lu (Food Science and Human Wellness)
The tropomyosin (TM) fractions of crab proteins may cause allergic reactions in individuals susceptible to allergies; however, efficient and safe methods by which to reduce such allergenicity are not currently available. Therefore, in this study, the effects of three different processing methods, i.e., microwave, ultrasound, and high temperature-pressure (HTP) treatments, on the digestion stability of TM from Chinese mitten crab muscle and the allergenicity of TM digestion products were explored. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis analysis showed that microwaving had little effect on the digestion stability of TM. In contrast, ultrasound and HTP treatments facilitated the degradation of TM. Similarly, Western blotting and inhibition ELISA indicated that the IgE-binding activity of TM was significantly reduced after treatment with ultrasound or HTP. Among the three different processing methods, HTP was the most effective method for improving digestibility of TM and reducing immunoreactivity. This finding provides new insights into treatments for crab allergies.